Trans / Meervoudige Gender Identiteit / Variant : onthaal, rechten, gezondheid, jeugd, werk... : iedereen goed geïnformeerd. - Dufrasne, Aurore; Nisol, Max; Pire, Maêl; Werler, Aurel (Bruxelles : Genres Pluriels, 2016)
Fonds Suzan Daniel (FSD)
Nederlands
Brochure